Effects of microsized and nanosized carbon fillers on the thermal and electrical properties of polyphenylene sulfide based composites. Issue 11 (6th February 2013) - Khan, Muhammad Omer; Leung, Siu N.; Chan, Ellen; Naguib, Hani E.; Dawson, Francis; Adinkrah, Vincent; Brostow, Witold; Schubert, Dirk; Blagojevic, Snja Lucic
<x xml:space="preserve">Abstract</x> Multifunctional polymer matrix composites (PMCs) exhibiting increased thermal and electrical conductivity can be achieved by adding conductive carbon‐based fillers in the polymer matrix. Emerging markets for thermally and electrically conductive PMCs include heat management devices in electronics, light emitting diodes, and/or photovoltaics cells as well as bipolar plates in fuel cells. In this study, the effects of microsized and nanosized carbon fillers [e.g., pitch‐based carbon fibers (CF), multiwalled carbon nanotubes (MWNT), and graphene nanoplatelets (GNPs)] on the multifunctional properties of polyphenylene sulfide (PPS) matrix composites were investigated. Among the three carbon‐based fillers, experimental results revealed that GNPs were the most effective fillers to promote the PMC's effective thermal conductivity (keff). The highest keff of 1.94 W/m K was attained by adding 30.0 wt% (i.e., 22.4 vol%) of GNPs in the PPS matrix. The nano‐sized MWNTs and GNPs had lower percolation threshold than the micron sized CFs to suppress the composite's electrical impedance. However, the coefficient of thermal expansion and the compressive elastic modulus of the composites were only slightly improved with the filler addition. The different levels of improvement in the composite's multifunctional properties can be related to the filler geometry, filler size, and the composite's phase morphology. POLYM. ENG. SCI., 53:2398–2406, 2013. © 2013 Society of Plastics Engineers